Development of Design, Explain, Development, And Evaluation-Project Based Learning (DEDEn-PjBL) Model in Stimulating Children's Creativity - Sadaruddin Sadaruddin; Arifin Ahmad; Baso Jabu; Syamsuardi Syamsuardi; Usman Usman; Hasmawaty Hasmawaty (Journal of Research and Multidisciplinary, 2023)
This research is research and development which aims to describe the level of need, prototype description, validity, practicality and effectiveness of the Design, Explain, Development, and Evaluation - Project Based Learning (PjBL) model in stimulating early childhood creativity. Data collection techniques through observation, interviews, and questionnaires. Data analysis techniques using descriptive and inferential data analysis. The research procedure begins with the investigation, design, realization, and test-evaluation-revision phases. The description of the needs analysis results shows that teachers need practical and effective learning models to stimulate children's creativity. The prototype description in the form of a model book and teacher's manual has been improved three times based on the input of expert validators and practitioners. It produces the DEDEn-PjBL model that can stimulate children's creativity. The results of the content validity test and the device's validity for all aspects are in the minimal category of "valid," so the DEDEn-PjBL model in stimulating children's creativity is declared valid. The results of the practicality test through the teacher's response questionnaire for all aspects are in the minimal category of "good," and the instrument for observing the implementation of the model shows that the average percentage of all aspects for five meetings is P >70% so that the DEDEn-PjBL model in stimulating children's creativity is declared practical. The effectiveness test results began with analyzing the pretest and post-test score data, which increased from the "low" to "very high" category. The data tested for normality with pretest results of 0.067 > Sig. 0.05 and posttest results in 0.081 > Sig. 0.05 so that the data is "normally distributed" after a hypothesis test, which shows the result tcount (14.714) > ttable (2.145), H0 rejected, and H1 accepted with a value of Sig. 0.00 > 0.05, which indicates that there is an influence of the DEDEn-PjBL model in stimulating children's creativity. The next step is the result of the mean N Gain Score is 0.7188 in the "high" category and a percentage value of 71.88% in the "quite effective" category. The N Gain test results show that the DEDEn-PjBL model is "quite effective" in stimulating children's creativity.